Organiza????es Empreendedoras do Terceiro Setor: desafios para a sobreviv??ncia no contexto do esporte educacional e de participa????o - Mota, Ana L??cia Castilho da (2015)
The third sector organizations (TSO) play an important social role in Brazil. With regard to educational and participation sports, partnerships with governments have been an important way to enable the democratization of their practice and to contribute to the human development of children and young people, especially those who are socially vulnerable, as guaranteed by law. Within this framework, the present study aimed at identifying the factors that influence the survival of TSO that work with educational and participation sports. The specific objectives aimed at identifying the TSO that work with educational and participation sports in the Greater S??o Paulo; analyzing how the facilitating factors and the critical factors influence the survival of these organizations; and devising a scheme that summarizes the influence of the main facilitating factors in the survival of these organizations. In order to do that, an exploratory and descriptive research was done, using the qualitative method, based on the phenomenological perspective. The chosen instrument for data collection was the interview supported by a semi-structured script, previously reviewed by two experts. We interviewed four founders and seven managers and / or coordinators, adding up to eleven interviews. The seven participating organizations of the research are affiliated with REMS (Sports Network for Social Change, in Portuguese). The data were analyzed using response categories according to Flores (1994), with the support of the software Atlas TI in the categorization of the results. The results were organized into four categories and these were split. The research concluded that among the main critical factors for the survival of the TSO are the heavy reliance on incentive funds, the lack of institutional financing; limited availability of funds for the communications, marketing and fundraising departments, the financing model under construction in Brazil, the legislation that needs to be realigned to the surrounding reality and the difficulty of measuring social outcomes. In relation to facilitating factors, the prevailing ones were the ability of articulation, institutional and sector dialogue with the government and the various segments of society, being part of networks, credibility and legitimacy of the organization, development of projects that have relevance and social impact, human resources identified with a social cause, the influence of the sector on the creation of public policies, the validation of the methodology, and the importance of the social entrepreneur.